2017
DOI: 10.1016/j.ekir.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

035 Epidemiology, Risk Factors and Survival of Aki Patients Treated by CRRT - A Study From Rural India

Abstract: and death were evaluated. The AKIN classification was used to define acute injury. Results: We identified 555 patients admitted to clinical and surgical wards, corresponding to 1,49% of the total number of patients hospitalized in the period, who was submited into hemodialyses and classified as having acute renal failure (lower incidence than that found in the literature-3.8%), of which 47,9% women and 52,1% men, with a mean age of 75,7 years. The double lumen catheter was the only type of vascular access used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is significant geographic variation in reported incidence of AKI. Along with the low incidences in China, the incidences of reported AKI in parts of Africa and Southern India are peculiarly low with most reports stating an incidence between 4 and 7% [28–31]. In contrast, the AKI incidence rate of 36–50% in South America was comparable with those observed in Europe and Northern America [32,33].…”
Section: Epidemiology Of Acute Kidney Injury In Covid-19mentioning
confidence: 91%
“…There is significant geographic variation in reported incidence of AKI. Along with the low incidences in China, the incidences of reported AKI in parts of Africa and Southern India are peculiarly low with most reports stating an incidence between 4 and 7% [28–31]. In contrast, the AKI incidence rate of 36–50% in South America was comparable with those observed in Europe and Northern America [32,33].…”
Section: Epidemiology Of Acute Kidney Injury In Covid-19mentioning
confidence: 91%
“…Sampathkumar et al collected and analyzed the data of 718 adult patients with COVID-19 from April to November 2020 and concluded that 7% developed AKI with a mortality of 44%. These patients with AKI had raised D-dimer and low albumin levels[16]. Sindhu et al carried out an observational study among 2650 COVID-19 patients between May 2020 and October 2020.…”
mentioning
confidence: 99%